Uptake of Resilient Crop Interventions to Manage Risks Through Climate-Smart Villages Approach in Nyando, Western Kenya - Recha, John W.M.; Radeny, Maren A.O.; Kinyangi, James; Kimeli, Philip (Springer, 2017)
The changing climate is a threat to the smallholder farmers. Poverty and limited livelihood options increase vulnerability to climate risks. To counter this, a partnership between research and development organizations and the Nyando rural community developed Climate-Smart Villages (CSVs) model to test local actions that ensure food security, promote adaptation and build resilience to climatic stresses. The purpose of the study was to explore the changes in farming practices made by households which are arising from the partnership. The study made use of household-level surveys for five years (2011–2015). The findings show increased use of terracing to conserve soil and water, intercropping, use of improved crop varieties, and households adopting three or more new crop types, greatly expanding on-farm choices for resilient varieties. The results can be used to showcase crop production practices suitable for adapting to the changing climate in rural communities.